Quality of Sleep Among the Patients of Congestive Cardiac Failure and Factors Associated with Poor Sleep Quality (Medical Forum Monthly, 2020)
Objective: To assess the quality of sleep in patients of congestive cardiac failure (CCF) and analyze the factors which can cause sleep disturbances.Study Design: Cross sectional (correlational) studyPlace and Duration of Study: This study was conducted at the cross sectional research was done at CMH Rawalakot from 1st January to 31st March 2018.Materials and Methods: The study subjects consisted of CCF patients with New York Heart Association Class III or IV. Sleep disturbance was analysed through Pittsburgh Sleep Quality Index (PSQI). Association of gender, age, smoking, duration of illness and body mass index were assessed with sleep disturbances.Results: Two hundred and sixty patients of CCF with NYHAC III or IV were included in the final analysis. 145 (55.7%) were male and 115 (44.3%) were female. Out of them, 117 (45%) had healthy sleep while 143(55%) had sleep disturbances at HA. After applying logistic regression we found that high BMI and long duration of illness was significantly associated with poor sleeping routines in patients with CCF.Conclusion: Sleep disturbances were a commonly found in patients suffering from congestive cardiac failure. Patients with high Body mass index and chronic illness were at higher risk of having sleep problems as compared to other patients.